An efficient circuit switching mechanism for Inter process communication in a transputer network - Taylı, Murat; Benmaiza, M. (IEEE, 1990)
Distributed real time system require interprocess communication (IPC) services to be not only reliable and efficient but also predictable. In such dynamic systems, predictability can only be achieved by proper architectural support that embodies adequate mechanisms and policies within the operating system. The authors present the design and implementation of predictable transport level communication services supported by the kernel of a real time distributed operating system (RTDOS). RTDOS IPC services are built on a hybrid platform, involving both message- and circuit-switching. Experimental results showed that RTDOS IPC was able to deliver millisecond-level connection times, guaranteed within the prescribed limits of system configuration.
Keywords: Circuits; Intelligent Networks; Real Time Systems; Operating Systems; Kernel; Communication Switching; Joining Processes; Communication System Traffic Control; Educational Institutions; Computer Networks; Distributed Real-Time Systems; Predictabiliq; Circuit-Switching; Transputer Nefworks; Real-Time Systems; Distributed Processing; Transputer Systems; Operating Systems (computers); Distributed Systems; Circuit-Switching Mechanism; Interprocess Communication; Transputer Network; Real Time System; Transport Level Communication; Real Time Distributed Operating System; RTDOS